Science Teachers’ Tendency to Use Some Teaching Methods and Techniques - Çirkinoğlu Şekercioğlu, Ayşe Gül; Saraç, Eren (Current Studies in Social Sciences IX-Güz, 2024)
The aim of this study is to examine the tendency of science teachers to use some teaching methods-techniques in their lessons. In the study, lecture, argumentation, demonstration, problem solving, project, observation, laboratory, question-answer, assignment, cooperative learning, case study, role playing methods-techniques were investigated. A total of 615 teachers working in Balıkesir and Manisa provinces participated in the study. In the study, an online 4-point rating questionnaire was published on the official websites of the Directorates of National Education and science teachers filled it out online. The questionnaire consisted of demographic information, participation in in-service training seminars, adequacy of the school in terms of teaching methods and techniques, and questions about teaching methods and techniques. According to the results of the research, the three most used teaching methods of the teachers are question-answer, assignment, laboratory, and the three least used methods are travelling-observation, role playing, and argumentation. Argumentation, problem solving, observation, question-answer, assignment method-techniques are preferred more by female teachers, while demonstration, project, laboratory, cooperative learning, case study, role playing method-techniques are preferred more by male teachers.